Toplam Kalite Yönetiminin Temel Kavramları - (:unkn) unknown (My University, 2002)
0

In our study, we tried to explain thinking fundamentals of Total Quality Management ( TQM ) which has been told too much since last years. This study has been done under eight topics. At the beginning, fundamentals that belongs to TQM had determined. At continuation it tried to be explained by using concrete datums. In our study, benefits that TQM has done to enterprise has explained however we have put opinions of the scientists against to TQM. At first part we tired to explain the importance which TQM attaches to people. At second part we explained effects of TQM on managing culture. At continuation, customer centered management mentality, top management leadership and responsibility, complete participation at management, motion by team, perpetual development and management according to aim subjects have tired to be explained.